Transformasi Manajemen Pemasaran di Era Ekonomi Digital dan Implikasinya terhadap Pembangunan Berkelanjutan - Judijanto, Loso; Wulansari, Retno (Jurnal Bisnis dan Manajemen West Science, 2025)
The transformation of marketing management in the digital economy era presents significant opportunities for enhancing sustainability and fostering development in Indonesia's creative economy. This study examines the relationships between digital marketing transformation, business sustainability, and sustainable development through a quantitative analysis involving 100 respondents. Data was collected using a Likert scale and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results indicate that digital marketing transformation positively and significantly impacts business sustainability (β = 0.65, p < 0.001) and sustainable development (β = 0.42, p < 0.001). Additionally, business sustainability has a significant positive effect on sustainable development (β = 0.50, p < 0.001). These findings underscore the potential of digital marketing strategies to not only improve business performance but also contribute to broader sustainability goals. The study highlights theoretical and practical implications, emphasizing the importance of digital tools in fostering economic, social, and environmental sustainability within Indonesia’s creative economy.